METTL3 facilitates immunosurveillance by inhibiting YTHDF2-mediated NLRC5 mRNA degradation in endometrial cancer - Lei Zhan; Jing Zhang; Jun-Hui Zhang; Xiao-Jing Liu; Bao Guo; Jia-Hua Chen; Zhen-Hai Tang; Wen-Yan Wang; Qing-Yuan Wang; Bing Wei; Yun-Xia Cao (BMC, 2023)
Abstract Background N6-methyladenosine (m6A) methylation is the most abundant chemical posttranscriptional modification of mRNA, and it is associated with the regulation of the immune response to tumors. However, the function of m6A modification in the immune response to endometrial cancer (EC) remains unknown. Our study investigated the immunological role of methyltransferase-like 3 (METTL3) in EC and the underlying molecular mechanism. Methods We investigated the correlation between the expression of METTL3 and CD8 by using an endometrial tissue microarray cohort. Next, we investigated the role and mechanism of METTL3 in the immune response to EC using a mouse tumor model and a CD8+ T cell-EC cell coculture system after METTL3 overexpression or depletion. Additionally, RNA immunoprecipitation (RIP), methylated RIP, and RNA stability experiments were used to investigate the mechanism underlying the function of METTL3 in immunosurveillance of EC. Results METTL3 levels were downregulated in EC patients, low levels of METTL3 were correlated with poor prognosis in EC patients. There was a positive correlation between METTL3 expression and CD8 expression. Overexpression of METTL3 in the EC cell and CD8+ T cell coculture system inhibited EC cell proliferation, migration, and promoted CD8+ T-cell proliferation, and in vivo, METTL3 overexpression increased CD8+ T cell proportions and inhibited EC progression; however, genetic depletion of METTL3 exerted the opposite effects. NLR family CARD domain-containing 5 (NLRC5) was identified as a target of METTL3-mediated m6A modification. The degradation of NLRC5 was increased by YTH domain-containing family 2 (YTHDF2). Conclusions Overall, METTL3, YTHDF2, and NLRC5 have potential to be the diagnostic and prognostic biomarkers for EC. METTL3 facilitated the m6A modifications of NLRC5 and inhibited its degradation through a YTHDF2-dependent mechanism in EC. Genetic overexpression of METTL3 attenuated the immune evasion of EC by promoting NLRC5-mediated immunosurveillance, suggesting that the METTL3/YTHDF2/NLRC5 axis is a promising target of immunotherapy in EC.